PENERAPAN METODE K-MEANS DALAM PENGKLASTERAN WILAYAH DI INDONESIA BERDASARKAN PEMBERIAN ASI EKSKLUSIF PADA BAYI - Zulia Imami Alfianti; Ginabila Ginabila; Ahmad Fauzi (Universitas Gunadarma, 2024)
Breast milk is a fluid that comes out of a mother's breast glands which contains a variety of nutrients needed to support the development and growth of toddlers. Exclusive breast milk (ASI) is breastfeeding that is not accompanied by any other food or drink supplementation except medication. Currently, exclusive breastfeeding is influenced by many factors, namely working mothers, low maternal education, incessant advertising about the use of formula milk, breast milk not coming in and many other factors causing not all babies to receive exclusive breast milk. In this research, regional clustering will be carried out based on the percentage of exclusive breastfeeding for 6 month old babies from 34 provinces in Indonesia. Clustering was carried out to group 34 provinces in Indonesia into provinces with high, medium and low cases. The results of this research are that 31% of provinces have the highest percentage, 40% have a medium percentage and 29% have a low percentage.